Técnicas grupales utilizadas en el proceso de enseñanza aprendizaje en estudiantes de educación general básica del colegio de bachillerato Dr. Modesto Chaves Franco de la ciudad de Santa Rosa, periodo lectivo 2014-2015. - Carrillo Viñas, Paola Alexandra (2014)
Group techniques are methodological tools that help teachers to facilitate teaching - learning process of a dynamic and active way, facilitating the attainment of skills for information and deepen, for the analysis of issues from other points of view and approaches, same application of these techniques allows to develop in students decision making, development of ideas and the development of creativity, application of a repertoire of group techniques allow the teacher to better learning rates, also give each student the opportunity to interact with faculty and peers, this interaction can put your knowledge to the test and contribute to the learning of others, and give each student the opportunity to clarify the concepts, provide an opportunity to synthesize the variety of experiences and data from classes, games, readings and other activities.